Andragogy Approach in Teaching Adults - Mahmudovna, Kasimova Guljahon (Miasto Przyszłości, 2023)
In this article, we will discuss the important aspects of the andragogy approach and the merits that its proponents promote. A few cases of its applications will also be discussed and critical analysis will be offered on how accepting the principles and precepts of andragogy can affect the future of education and industries moving forward.